The Role of Type 2 Inflammation in Schistosoma-Induced Pulmonary Hypertension - Mickael, Claudia S.; Graham, Brian B. (Frontiers in Immunology, 2019)
Approximately 5% of individuals chronically infected with Schistosoma mansoni develop pulmonary hypertension (PH). The disease is progressive and often fatal, and treatment options are palliative, not curative. Recent studies have unraveled major players of the Th2 inflammation axis in the Schistosoma-induced PH pathology using murine models and studying human samples. TGF-β signaling is a link between the Type 2 inflammation and vascular remodeling, and specifically Thrombospondin-1 (TSP-1) is upregulated by the inflammation and activates TGF-β. Overall, the current model for the pathogenesis of Schistosoma-induced PH is that deposition of Schistosoma mansoni eggs in the pulmonary vasculature results in localized Th2 inflammation, leading to TGF-β activation by TSP-1, and the active TGF-β then results in vascular remodeling and PH.